“Paving the way for student-led publication: Development and implementation of a course in Information Systems with open educational resources - Althaus, Maike; Müller, Michelle; Bartelheimer, Christian; Kundisch, Dennis

Assessing the impact of organizational culture on workarounds: A maturity model - Bartelheimer, Christian; Reineke, Malte

Hybridizing Target- and SHAP-encoded Features for Algorithm Selection in Mixed-variable Black-box Optimization - Dietrich, K.; Prager, R.; Doerr, C.; Trautmann, Heike (Parallel Problem Solving from Nature — PPSN XVIII)

Michael Basse / Marcel Nieden (Hg.): Cajetan und Luther. Rekonstruktion einer Begegnung. Tübingen 2021 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Lorenz Trein: Beobachtungen der Säkularisierung und die Grenzen der Religion. Tübingen 2023 - Schroeter-Wittke, Harald (Jahrbuch für Evangelische Kirchengeschichte des Rheinlandes)

Highly Efficient Quenching of Singlet Oxygen by DNA Origami Nanostructures - Garcia-Diosa, Jaime Andres; Grundmeier, Guido; Keller, Adrian (Chemistry – A European Journal)
DNA origami nanostructures (DONs) are able to scavenge reactive oxygen species (ROS) and their scavenging efficiency toward ROS radicals was shown to be comparable to that of genomic DNA. Herein, we demonstrate that DONs are highly efficient singlet oxygen quenchers outperforming double‐stranded (ds) DNA by several orders of magnitude. To this end, a ROS mixture rich in singlet oxygen is generated by light irradiation of the photosensitizer methylene blue and its cytotoxic effect on Escherichia coli cells is quantified in the presence and absence of DONs. DONs are found to be vastly superior to dsDNA in protecting the bacteria from ROS‐induced damage and even surpass established ROS scavengers. At a concentration of 15 nM, DONs are about 50 000 times more efficient ROS scavengers than dsDNA at an equivalent concentration. This is attributed to the dominant role of singlet oxygen, which has a long diffusion length and reacts specifically with guanine. The dense packing of the available guanines into the small volume of the DON increases the overall quenching probability compared to a linear dsDNA with the same number of base pairs. DONs thus have great potential to alleviate oxidative stress caused by singlet oxygen in diverse therapeutic settings.

Children and young people’s ICT experiences in school education: Participatory research design to engage children and young people as experts in research - Labusch, Amelie; Eickelmann, Birgit; Casamassima, Gianna; Drossel, Kerstin; Gudmundsdottir, G.B.; Kazani, A.; Mifsud, L.; Symeonaki, M.; Teidla-Kunitsõn, G. (Understanding the everyday digital lives of children and young people)

Perspectives of children and young people on their education as preparing for their future in the digital age: In-depth qualitative study in five European countries. - Eickelmann, Birgit; Barbovschi, M.; Holmarsdottir, H.B.; Parsanoglou, D.; Sisask, M.; Labusch, Amelie (Understanding the everyday digital lives of children and young people)

Theorien des digitalen Kapitalismus - Fuchs, Christian (Handbuch Medientheorien im 21. Jahrhundert)

On the Potential of Multi-objective Automated Algorithm Configuration on Multi-modal Multi-objective Optimisation Problems - Preuß, Oliver Ludger; Rook, Jeroen; Trautmann, Heike (Applications of Evolutionary Computation)

Using Reinforcement Learning for Per-Instance Algorithm Configuration on the TSP - Seiler, Moritz; Rook, Jeroen; Heins, Jonathan; Preuß, Oliver Ludger; Bossek, Jakob; Trautmann, Heike (2023 IEEE Symposium Series on Computational Intelligence (SSCI))

Grundlagen einer Ethik des Radikalen Digitalen Humanismus - Fuchs, Christian (Digitalisierte Massenkommunikation und Verantwortung)

Critical Perspectives on Digital Capitalism: Theories and Praxis. Introduction to the Special Issue - Fuchs, Christian; Arslan, Sevda Can; Allmer, Thomas (tripleC: Communication, Capitalism & Critique)

Vincent Mosco’s Critical-Humanist Political Economy of Communication - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Preface - Fuchs, Christian (Yuqi Na: The Chinese Internet. Political Economy and Digital Discourse)

Media, Economy and Society: A Critical Introduction. - Christian, Fuchs

Politisch? Poetisch? Persönlich? Barbara Strozzis „Il lamento“ zwischen Selbstausdruck und politischer Positionierung - Tumat, Antje (Barbara Strozzi (1619-1677). Musik und Diskurs im Venedig des Seicento)

“It’s like I got a new pair of glasses”: Reflections on sense of self, home, and belonging among transnational students in short-term study abroad programs - Müller, Mareike (Study Abroad Research in Second Language Acquisition and International Education)
This study focuses on a specific group of sojourners that has thus far remained rather unexplored in the context of study-abroad research, namely, students with extensive prior experiences of living in, traveling to, and/or familial ties with target-language mediated communities. To this end, this study examines data obtained through episodic interviews with three American students, who grew up in close contact with German-speaking communities and studied abroad in Austria for four weeks. By means of thematic analysis, the pre-study abroad sojourn motives and reflections on sense of self, home, and belonging are contrasted with these students’ immediate and delayed post-study abroad accounts. The results shed light on both the challenges young adults grapple with due to their international biographies and the transformative effects students attribute to their short-term sojourns with regard to redefining who they are and what meaning different places of home and heritage have within their individual trajectories.

Towards a computational architecture for co-constructive explainable systems - Booshehri, Meisam; Buschmeier, Hendrik; Cimiano, Philipp; Kopp, Stefan; Kornowicz, Jaroslaw; Lammert, Olesja; Matarese, Marco; Mindlin, Dimitry; Robrecht, Amelie; Vollmer, Anna-Lisa (Proceedings of the 2024 Workshop on Explainability Engineering (ExEn’24))

VACO: a Multi-perspective Development of a Therapeutic and Motivational Virtual Robotic Agent for Concentration for children with ADHD - Richter, Birte; Petras, Ira-Katharina; Vollmer, Anna-Lisa; Luong, Ayla; Siniatchkin, Michael; Wrede, Britta (arXiv:2405.03354)
In this work, we present (i) a novel approach how artificial intelligence can support in the therapy for better concentration of children with Attention Deficit Hyperactivity Disorder (ADHD) through motivational attention training with a virtual robotic agent and (ii) a development process in which different stakeholders are included with their perspectives. Therefore, we present three participative approaches to include the perspectives of different stakeholders. An online survey (Study I) was conducted with parents in Germany with the aim of ascertaining whether they would use software to promote their children's attention, what influences their attitude towards using it, and what requirements it would have to meet. About half of the parents would be willing to use software to promote attention. To develop the software as close to practice as possible, one of the developers took part in an intensive training for ADHD with the aim of testing which of the elements are technically feasible. Afterward, a first prototype was presented to clinicians (Study II) to make further adjustments. A first feasibility test (Study III) was conducted with the end users to check if the system works and if children and adolescents can use it. Attentional performance software offers multiple opportunities in the treatment of ADHD if the system is adapted to the needs of the practitioner and end user. This development process requires a lot of time and close interdisciplinary collaboration.